PENGARUH SELF EFFICACY, LOCUS OF CONTROL DAN KOMITMEN ORGANISASI TERHADAP KINERJA PENDAMPING SOSIAL - Rizana, Dani (P4M STIE Putra Bangsa, 2019)
The purpose of this study was to study the organizational commitment, organizational culture and environment towards the Family Hope (PKH) companion program at the Social Service Office of the PPKB Kebumen Regency. This research is a survey research with the influence of Self efficacy (X1), locus of control (X2), and organizational commitment (X3) on the performance of companion in the Social Service Office of Kebumen Regency PPKB. The population is all companions taking 240 people, while the sample is taken 150 companions. The collection of data using a questionnaire that has collected validity and reliability using the help of the SPSS program for Windows. The data collected from the results of the questionnaire were then analyzed using regression analysis, which had previously been subjected to analysis prerequisite tests using normality, multicollinearity, and heterokedasticity tests. After analyzing the data, the following results and conclusions are obtained: (1) self efficacy influences the performance of the companion. (2) The locus of control shows a positive and significant effect on the performance of the companion. (3) Organizational commitment shows a positive and significant impact on the performance of the companion. (4) Self efficacy, locus of control and organizational commitment have a significant (simultaneous) effect on the performance of PKH Social Assistance in Kebumen District and provide a 56.10% increase in the performance of PKH companions (RÂ² = 0.561), according to variable needs variables other than these three variables amounted to 43.90%. Keywords: Self of efficacy, locus of control and commitment